2007
DOI: 10.1369/jhc.6a7116.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Alpha 7 Nicotinic Acetylcholine Receptors by Bipolar, Amacrine, and Ganglion Cells of the Rabbit Retina

Abstract: Cholinergic agents affect the light responses of many ganglion cells (GCs) in the mammalian retina by activating nicotinic acetylcholine receptors (nAChRs). Whereas retinal neurons that express β2 subunit-containing nAChRs have been characterized in the rabbit retina, expression patterns of other nAChR subtypes remain unclear. Therefore, we evaluated the expression of α7 nAChRs in retinal neurons by means of single-, double-, and triple-label immunohistochemistry. Our data demonstrate that, in the rabbit retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 75 publications
5
47
0
Order By: Relevance
“…Following the protocol of Dmitrieva et al (2007), isolated retinas from four salamander eyes were homogenized in four volumes of ice-cold lysis buffer: PBS containing 1% NP-40, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), protease inhibitor cocktail (1:30), and incubated at 4°C for 30 minutes, then centrifuged (15,000g at 4°C for 30 minutes). The supernatant was retained and mixed with an equal amount of sample buffer.…”
Section: Western Blottingmentioning
confidence: 99%
“…Following the protocol of Dmitrieva et al (2007), isolated retinas from four salamander eyes were homogenized in four volumes of ice-cold lysis buffer: PBS containing 1% NP-40, 0.5% sodium deoxycholate, 0.1% sodium dodecyl sulfate (SDS), protease inhibitor cocktail (1:30), and incubated at 4°C for 30 minutes, then centrifuged (15,000g at 4°C for 30 minutes). The supernatant was retained and mixed with an equal amount of sample buffer.…”
Section: Western Blottingmentioning
confidence: 99%
“…In isolated/cultured porcine and salamander RGCs, the neuroprotective effects of nAChR agonists against glutamate-induced excitotoxicity are mediated by the Ca 2+ -phosphatidylinositol 3-Akt-Bcl2 and NF-κβ cell survival signaling pathway, and via the mitogen-activated protein kinase apoptosis pathway 511 . Previous studies have demonstrated that α7-nAChRs are expressed in retinal bipolar, amacrine, and ganglion cells in normal mice and rabbits 1214 . However, it is unclear whether activation of α7-nAChRs exerts a neuroprotective role in a chronic in vivo rat glaucoma model produced by episcleral vein cautery.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence supports the idea that there may be a specific involvement of the sensory visual system. A primary retinal involvement appears plausible since cholinergic and glutamatergic systems are impaired in AD [7] . In the retina, light-activated photoreceptors transmit signals to bipolar and ganglionar cells via glutamate and aspartate neural transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In the retina, light-activated photoreceptors transmit signals to bipolar and ganglionar cells via glutamate and aspartate neural transmission. Furthermore, amacrine cells, which are specifically involved in chromatic light stimulus transmission, utilize acetylcholine as a neurochemical mediator [7] .…”
Section: Introductionmentioning
confidence: 99%